1977
DOI: 10.1107/s0021889877013545
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of integrated intensity near the absorption edge with synchrotron radiation

Abstract: By the use of synchrotron radiation at Stanford, the integrated reflexion intensities were measured on 222, 333 and 555 reflexions from a GaAs single-crystal plate in the energy region very near the Ga K absorption edge. The energy dependence of the intensities agreed reasonably with the corresponding calculated curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Then, by the best use of an SSD (solid-state detector), it was shown that the determination of the anomalous-scattering factors as functions of energy and some applications of these factors such as polarity determination are feasible in a typical laboratory Hosoya, 1975;Fukamachi & Hosoya, 1975;Fukamachi, Hosoya & Okunuki, 1976a,b;Fukamachi, Hosoya, Kawamura & Okunuki, 1977. Concurrently, the advent of synchrotron radiation has opened great possibilities in this field (Bonse & Materlik, 1976;Phillips, Wlodawer, Yevitz & Hodgson, 1976;Phillips, Wlodawer, Goodfellow, Watenpaugh, Sieker, Jensen & Hodgson, 1977;Fukamachi, Hosoya, Kawamura & Hastings, 1977;Fukamachi, Hosoya, Kawamura, Hunter & Nakano, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Then, by the best use of an SSD (solid-state detector), it was shown that the determination of the anomalous-scattering factors as functions of energy and some applications of these factors such as polarity determination are feasible in a typical laboratory Hosoya, 1975;Fukamachi & Hosoya, 1975;Fukamachi, Hosoya & Okunuki, 1976a,b;Fukamachi, Hosoya, Kawamura & Okunuki, 1977. Concurrently, the advent of synchrotron radiation has opened great possibilities in this field (Bonse & Materlik, 1976;Phillips, Wlodawer, Yevitz & Hodgson, 1976;Phillips, Wlodawer, Goodfellow, Watenpaugh, Sieker, Jensen & Hodgson, 1977;Fukamachi, Hosoya, Kawamura & Hastings, 1977;Fukamachi, Hosoya, Kawamura, Hunter & Nakano, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The stringent requirements on the saiiiple are likely to keep the number of accessible cases limited, and the bulk of the experimental f ' will be based on calculations from the absorption coefficients. A t the moment accurate measurements extending to long wavelengths and high-resolution studies near the absorption edges are the critical points in quest of more reliable values of f', and here the tunable synchrotron radiation [15] and novel monochromator constructions [35] are opening new avenues to both directions.…”
Section: Disciissiorimentioning
confidence: 99%
“…The direct method has been widely used by several investigators to evaluate f ¼ and f ¼¼ . This method is based on (i) the measurement of the refractive index of the specimen of interest, (ii) the determination of intensities of Bragg reflections [23] and (iii) X-ray interferometry [24] from which f ¼ and f ¼¼ values are calculated. The principal advantage of this method is that it can yield absolute values of f ¼ and f ¼¼ .…”
Section: Introductionmentioning
confidence: 99%